2018
DOI: 10.1186/s12890-018-0675-8
|View full text |Cite
|
Sign up to set email alerts
|

Latent class analysis to define radiological subgroups in pulmonary nontuberculous mycobacterial disease

Abstract: BackgroundNontuberculous mycobacterial (NTM) pulmonary disease has conventionally been classified on the basis of radiology into fibrocavitary and nodular-bronchiectatic disease. Whilst being of great clinical utility, this may not capture the full spectrum of radiological appearances present. The aim of this study was to use latent class analysis (LCA) as an unbiased method of grouping subjects with NTM-pulmonary disease based on their CT features and to compare the clinical characteristics of these groups.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…LCA has recently been tested and found to be useful for identifying latent classes (subgroups) of radiological findings within multivariable datasets [22][23][24]. In this study, two radiological subgroups were identified based on the LCA of CT findings of patients with COVID-19 pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…LCA has recently been tested and found to be useful for identifying latent classes (subgroups) of radiological findings within multivariable datasets [22][23][24]. In this study, two radiological subgroups were identified based on the LCA of CT findings of patients with COVID-19 pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…Systems for scoring NTM-PD radiology have been developed but are not widely used outside of research studies or specialist centres. [23][24][25] copyright.…”
Section: Radiologicalmentioning
confidence: 99%
“…This characterization of bronchial alterations as an important radiological finding of NTM-LD is relevant for the diagnosis and also for the patient recovery. A study by Cowman et al (2018) suggested that bronchiectasis interfered with the duration of the disease and was associated with severe lung disease prognosis 47 .…”
Section: Radiological Diagnosismentioning
confidence: 99%